Academic Information System on The Prince Jayakarta Junior High School Student Assessment System - Haq, Fesa Asy Syifa Nurul; Muliati, Vika Febri; Rahman, Abdu; Zarlis, Muhammad; Darusalam, Ucuk; Siregar, Nurhayati (Universitas Bina Sarana Informatika, 2025)
Information technology has supported the development of quality school services throughout the world. However, there are still many schools that have not used it optimally, especially in Indonesia, for example at Prince Jayakarta Bekasi Middle School. As in general, schools only use Ms. Word and Ms. applications . Excel. This resulted in different assessment formats and errors when filling in grades into the report card format. The academic information system application developed in this study uses the PHP, HTML, and MySQL programming languages and is named SIAP, which means eighteen academic information systems. The purpose of making this application is so that students / parents of students can receive school assessment information in a precise, fast and accurate manner. Teachers can also use the facility to process student scores so that they are well integrated and summarized as data for the Principal to make policies. This application can be opened on any browser platform, making it easier for users to access it anywhere and anytime.